Impact of Oxidative Stress on Male Reproduction in Domestic and Wild Animals - Eliana Pintus; José Luis Ros-Santaella (MDPI AG, 2021)
Oxidative stress occurs when the levels of reactive oxygen species (ROS) overcome the antioxidant defenses of the organism, jeopardizing several biological functions, including reproduction. In the male reproductive system, oxidative stress not only impairs sperm fertility but also compromises offspring health and survival, inducing oxidative damage to lipids, proteins and nucleic acids. Although a clear link between oxidative stress and male fertility disorders has been demonstrated in humans and laboratory rodents, little information is available about the implications of impaired redox homeostasis in the male fertility of domestic and wild animals. Therefore, this review aims to provide an update regarding the intrinsic and extrinsic factors that are associated with oxidative stress in the male reproductive system and their impact on the reproductive performance of domestic and wild animals. The most recent strategies for palliating the detrimental effects of oxidative stress on male fertility are reviewed together with their potential economic and ecological implications in the livestock industry and biodiversity conservation.